Deskripsi KesalahanISiswa dalam Menyelesaikan Soal Operasi Hitung Pecahan - Geri Dwi Nugraha; Indrie Noor Aini (Jurnal Ilmiah Dikdaya, 2022)
The purpose of this study was to describe the errors made by students in solving fractional arithmetic operations. This research uses descriptive research using a qualitative approach. The research was conducted at SDN Pamanukan 1 in class V as many as 10 students. In this study, the technique used is a data analysis technique in the form of description test questions which are carried out to observe the material for fractional arithmetic operations. Based on the results and discussion shows that students make mistakes in understanding concepts and errors in counting. Errors in understanding the concept stated that students made errors with a percentage of 96.6% and errors in counting stated that students made errors with a percentage of 73.3%. Student errors in understanding concepts include errors in adding up a fraction, errors in equating the denominator, errors in converting mixed fractions into ordinary fractions. While errors in counting include errors in adding up but students perform the operation of fractions by multiplying.